The Student City. Strategic Planning for Student Communities in EU Cities - Leo Van den Berg; Antonio Paolo Russo (European Regional Science Association (ERSA), 2003)
Students are the citizens and the high-skilled working class of tomorrow. They keep cities lively and diverse. They are the main consumers of cultural and recreational facilities. They have a distinct expenditure pattern that in some cases is crucial to support the economy of whole cities or specific neighborhoods. Increased international students' mobility is a major vector of socio-economic integration between regions of Europe. However, the conditions for a full integration of student communities in local communities are not always met. Students are still an "invisible population", with little space in local policy, no decision power, and an ambiguous role in social development. The importance of human capital as a determinant of the competitiveness of cities demands pro-active, integral city policies targeting this community. Whereas education programs are generally carried out at the national or regional level, they often neglect the "urban" dimension of the issue, forgetting that human capital is highly mobile, and that it needs to be attracted, welcomed and managed locally. A new EURICUR study intends to contribute to the elaboration of a framework for comprehensive strategic action aiming at the integration of student communities in urban development. To this aim, the essential characteristics of the relationship of students with host communities in European cities have been analysed, as well as the role of higher education institutions and other actors in building the "student-friendly" city. This framework has been tested in nine European cities: Rotterdam, Utrecht and Eindhoven (NL), München (D), Lyon and Lille (F), Venice (I), Birmingham (GB) and Helsinki (SF). A wide typology of situations and problems has been found, with some common points that are clear indications for policymakers. To name a few, the importance that firms today attach to flexible, locally-oriented education curricula, which puts increased pressure on HEIs to work together with local governments in the definition of their supply; and the importance of diverse, versatile student communities in building the creative city, which underscores the role of campus planning but also solicits a socially responsible attitude of firms in enhancing the quality of education facilities.
Keywords: 330